Mechanical properties of an epoxy-based coating reinforced with silica aerogel and ammonium polyphosphate additives. (10th January 2022) - Riahipour, Ramin; Nemati, Mohammad Saber; Zadehmohamad, Mehdi; Abadyan, Mohammad reza; Tehrani, Mehran; Baniassadi, Majid
Flame retardant (FR) additives may degrade polymers' mechanical performance. In this work, FR epoxy composites fabricated based on two popular FR agents of ammonium polyphosphate (APP) and silica aerogel (SAG) are investigated. Several mechanical properties of these composites, including compressive, micro-hardness, and Izod impact, were investigated for different filler loadings. Although the addition of 10 vol.% APP improved compressive modulus, yield strength, and micro-hardness, it degraded the impact strength. The incorporation of SAG made the composites more ductile, improved the impact strength, but deteriorated their compressive properties. Samples containing both SAG and APP demonstrated synergetic effects evident by their enhanced compressive properties and hardness. The findings of this study can guide the design of epoxies with both exceptional FR and mechanical performance.